DNA single-strand break-induced DNA damage response causes heart failure - Tomoaki Higo (Nature Portfolio, 2017)
DNA damage response (DDR) is activated in cardiomyocytes of the failing heart, but the type of DNA damage leading to DDR is unclear. Higoet al. show that in mice heart failure is caused in part by unrepaired DNA single-strand breaks in cardiomyocytes, which activate persistent DDR and trigger an NF-κB-dependent cardiac inflammation.